Shelf life: neritic habitat use of a turtle population highly threatened by fisheries - Snape, Robin T. E.; Broderick, Annette C.; Cicek, Burak A.; Fuller, Wayne J.; Glen, Fiona; Stokes, Kimberley; Godley, Brendan J. (Wiley-Blackwell, 2016)
Aim It is difficult to mitigate threats to marine vertebrates until their habitat use is understood. We report on a decade of satellite tracking loggerhead turtles (Caretta caretta) from an important nesting site to determine priority habitats for their protection in a region where they are known to be heavily impacted by fisheries. Location Cyprus, Eastern Mediterranean. Method We tracked 27 adult female loggerheads between 2001 and 2012 from North Cyprus nesting beaches. To eliminate potential biases, we included females nesting on all coasts of our study area, at different periods of the nesting season and from a range of size classes. Results Foraging sites were distributed over the continental shelf of Cyprus, the Levant and North Africa, up to a maximum distance of 2100 km from nesting sites. Foraging sites were clustered in (1) near-shore waters of Cyprus and Syria, (2) offshore waters of Egypt and (3) offshore and near-shore regions of Libya and Tunisia. The North Cyprus and west Egypt/east Libyan coasts are important areas for loggerhead turtles during migration. Movement patterns within foraging sites strongly suggest benthic feeding in discrete areas. Early nesters visited other rookeries in Turkey, Syria and Israel where they likely laid further clutches. Tracking suggests minimum annual mortality of 11%, comparable to other fishery-impacted loggerhead populations. Main conclusions This work further highlights the importance of neritic habitats of Libya and Tunisia as areas likely used by loggerhead turtles from many of the Mediterranean rookeries and where the threat of fisheries bycatch is high. Our tracking data also suggest that anthropogenic mortalities may have occurred in North Cyprus, Syria and Egypt; all within near-shore marine areas where small-scale fisheries operate. Protection of this species across many geopolitical units is a major challenge and documenting their distribution is an important first step.
Keywords: bycatch; Caretta; conservation; distribution; fisher; foraging; migration; mortality; telemetry; threat